Egyptian Fauna in Nilotic Scenes - Voltan, Eleonora (My University, 2023)
The land of Egypt was fought over and incorporated into Rome's mentality in a similar way to the conquest of Greece: the conquered subjugated the conqueror and, through its culture, bound him to itself in a way that was as subtle as it was indissoluble. In fact, Roman swords and war strategies were disarmed by the knowledge and exotic fascination of the Nilotic land, to the extent that the ferment created by the influence and direct confrontation with this millenary civilisation led to the creation of a peculiar material culture inspired by Egypt through the Roman perspective. An effective proof of this is the elaboration of nilotic landscapes which, from the first testimonies of the late Republican period, became popular in the Imperial period, becoming a real fashion driven by the more intense contacts between Egypt and the Empire, especially with the annexation of the former to the Roman territories. Within the repertoire of Roman Nilotic representations, there are some recurrent iconographic elements that "mark" this figurative typology. In addition to the flora, the representation of the fauna living on the banks of the Egyptian river plays a fundamental role in the iconography of the Roman Nilotic. The aim of this paper is to draw attention to the different types of animals that animate these images, such as crocodiles, hippopotamuses, ibises, etc., their manner of representation, especially between the 1st and 2nd centuries AD, as well as their representation as an abstraction of exoticism, rarity and distance associated with the Roman province of Egypt. Finally, some of the main compositional schemes relating to the encounter/confrontation between the Nilotic fauna and the pygmies, central characters in the Nilotic scenario, will be briefly considered.
Keywords: Arqueología; Egypt; Fauna; Roman iconography; Nile; Pygmy